Paediatric Spinal Anaesthesia (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Spinal anesthesia was probably the earliest form of regional anesthesia that was considered a useful practice for children. Since that time, spinal anesthesia have become an important anesthetic technique for reducing the incidence of postoperative apnea in premature and ex-premature infants .Spinal anaesthesia provides a good alternative to general anaesthesia in newborns with increased anaesthesia-related risk, and for infants undergoing lower abdominal or lower extremity surgery during the first 6 months of life. It is most successful as a single shot technique, limited to surgery lasting less than ninety minutes. Spinal anaesthesia in children requires the technical skills of experienced anaesthesia providers.JBSA 2012; 25(2): 71-74